Factor structure of the integrated training of elite athletes - representatives of mountain sports - Zh.L. Kozina; O.A. Ryepko; Kr. Prusik; M. Cieślicka (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The purpose of this study was to identify the characteristics of the factor structure of the readiness of mountaineers and climbers of different specializations. The study involved 26 athletes, among them - 10 masters of sports of international class (speed climbing ), 10 masters of sports of international class ( climbing difficulty) and 6 world-class climbers. The age of the athletes was 19-22 years. Identified 10 factors in the overall readiness of the surveyed athletes. It is shown that the most prominent climbers factors are adaptive capacity of the cardiovascular system, special endurance. Do climbers ( climbing difficulty) - relative strength, stability, reaction speed, arm strength and the press. Do climbers ( climbing speed) - spigot size hand, the mobility of the nervous system, the reaction rate. Shows the complexity of the manifestations of power-speed in relation to the performance of morphological and functional characteristics and capabilities of psychophysiological representatives of mountain sports. Found that the development of the power-speed positive effect on the improvement of psycho-physiological regulation of the body. The obtained data on the characteristics of the severity of different factors in representatives of different types of rock climbing and mountaineering can be used to predict future specialization novice climbers.